Alternative kinship structures, resilience and social support among immigrant trans Latinas in the USA. Issue 1 (2nd January 2019) - Hwahng, Sel J.; Allen, Bennett; Zadoretzky, Cathy; Barber, Hannah; McKnight, Courtney; Des Jarlais, Don
Abstract: Latinas comprise the largest racial/ethnic group of trans women (male-to-female transgender people) in New York City, where HIV seroprevalence among trans Latinas has been found to be as high as 49%. Despite this population's high risk of HIV, little is known about resilience among trans Latinas that may provide protective health factors. Six focus groups and one in-depth interview were conducted with 34 low-income trans/gender-variant people of colour who attended transgender support groups at harm reduction programmes in New York City. This paper reports on data from 13 participants who identified as immigrant trans Latinas. Focus groups were coded and analysed using thematic qualitative methods. The majority of immigrants were undocumented but reported having robust social support. Unique characteristics of immigrant trans Latinas included alternative kinship structures and sources of income. Social creativity was used to develop achievable ways in which to improve their health outcomes. Resilience was evident in informal kinship dynamics, formal support groups, gender-transition, educational access and skills training and substance use reduction. Individual-level resilience increased as a result of strong community-level resilience.